The Somatic Auditory Visual Intellectual Learning Model Assisted by Mystery Card Media to Enhance Science Knowledge Competence in Grade IV Students - Ni Putu Manik Candra Dewi; Ni Wayan Suniasih; Anak Agung Ayu Dewi Sutyaningsih (Jurnal Pedagogi dan Pembelajaran, 2025)
The critical thinking ability of students in elementary schools is still low. This is because teachers do not use learning models that can stimulate students' critical thinking skills. This study aims to analyze the effect of the Somatic auditory visual intellectual learning model assisted by mystery card media on fourth grade students. This type of research is a quasi-experimental study with a non-equivalent control group design. The population of the study was all 316 fourth grade students. The research sample of 59 people was determined using the cluster random sampling technique, 29 people in class IV B as the experimental group and 30 people in class IV B as the control group. Science knowledge competency data were collected using the test method, the usual multiple choice objective type. The research instrument used a multiple choice test. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. The results of the hypothesis test showed that H0 was rejected and H1 was accepted. So it can be concluded that the somatic, auditory, visual, intellectual learning model assisted by mystery cards has a significant effect on the science knowledge competency of fourth grade students. The implications of this study are expected to be a new reference for teachers in implementing the SAVI learning model in the learning process.